Politeness Utterances Analysis of Comment Structure on Adrian Brody’s Oscar Victory in Instagram from BBC News - Dinda Arifah Rahmawati; Sigit Haryanto (UIN Kiai Ageng Muhammad Besari Ponorogo, 2026)
This study examines politeness and impoliteness strategies in Instagram comments responding to BBC News’ post about Adrian Brody’s Oscar win. Using a qualitative pragmatic approach, the study analyzes user-generated comments and classifies them based on Brown and Levinson’s politeness theory, while sarcastic or ridiculing expressions are interpreted using Culpeper’s impoliteness framework. The data consist of publicly available comments that are relevant to the post and contain analyzable linguistic features, while irrelevant or non-linguistic comments are excluded. The findings reveal four main strategies: positive politeness, negative politeness, bald-on-record, and mock politeness. Positive politeness appears in supportive and congratulatory comments, while negative politeness is used to express criticism in a mitigated manner. Bald-on-record strategies convey direct and often harsh criticism, whereas mock politeness reflects sarcasm through indirect expressions. The results also indicate that users’ responses are influenced by the controversy surrounding Brody’s behavior and by the interactive nature of Instagram, which encourages spontaneous and emotionally driven communication. This study contributes to digital pragmatics by demonstrating how politeness and impoliteness coexist and interact in shaping online discourse.